SURAT PERJANJIAN 7 JANUARI 1681: EDISI DIPLOMATIK NASKAH - Tendi Tendi (IAIN Syekh Nurjati Cirebon, 2020)
As an area with a long history, Cirebon has a number of different historical phases. One of the phases in Cirebon history which is the most rarely discussed is the colonial phase and hence this period is often referred tas the phase with pĕtĕng history (dark history). The Cirebon colonial period began with the signing of the January 7, 1681 Agreement, which then brought Cirebon into the arms of the Vereenigde Oost Indies Compagnie (VOC) hegemony. This article seeks to explain the description or identity of the manuscript of the 7 January 1681 Testament and its historical journey. In addition, this article also aims to present the transcript of the text of the Letter of Agreement of January 7, 1681 which has a Jawi script and Malay in a diplomatic edition. In this paper, the philological approach is used to explore the text of the agreement. The philological method used here is the transfer of literary texts in the diplomatic edition.Keywords: agreement, Cirebon, VOC, pĕtĕng history, Jawi Script, Malay Language